7T MRI Differentiates Remyelinated from Demyelinated Multiple Sclerosis Lesions. Issue 4 (2nd September 2021) - Kolb, Hadar; Absinta, Martina; Beck, Erin S.; Ha, Seung‐Kwon; Song, Yeajin; Norato, Gina; Cortese, Irene; Sati, Pascal; Nair, Govind; Reich, Daniel S.
Abstract : Objective: To noninvasively assess myelin status in chronic white matter lesions of multiple sclerosis (MS), we developed and evaluated a simple classification scheme based on T1 relaxation time maps derived from 7‐tesla postmortem and in vivo MRI. Methods: Using the MP2RAGE MRI sequence, we classified 36 lesions from 4 postmortem MS brains as "long‐T1, " "short‐T1, " and "mixed‐T1" by visual comparison to neocortex. Within these groups, we compared T1 times to histologically derived measures of myelin and axons. We performed similar analysis of 235 chronic lesions with known date of onset in 25 MS cases in vivo and in a validation cohort of 222 lesions from 66 MS cases, investigating associations with clinical and radiological outcomes. Results: Postmortem, lesions classified qualitatively as long‐T1, short‐T1, and mixed‐T1 corresponded to fully demyelinated, fully remyelinated, and mixed demyelinated/remyelinated lesions, respectively ( p ≤ 0.001). Demyelination (rather than axon loss) dominantly contributed to initial T1 prolongation. We observed lesions with similar characteristics in vivo, allowing manual classification with substantial interrater and excellent intrarater reliability. Short‐T1 lesions were most common in the deep white matter, whereas long‐T1 and mixed‐T1 lesions were prevalent in the juxtacortical and periventricular white matter ( p = 0.02) and were much more likely to have paramagnetic rims suggesting chronic inflammation ( p < 0.001). Older age at the time of lesion formation portended less remyelination ( p = 0.007). Interpretation: 7‐tesla T1 mapping with MP2RAGE, a clinically available MRI method, allows qualitative and quantitative classification of chronic MS lesions according to myelin content, rendering straightforward the tracking of lesional myelination changes over time. ANN NEUROL 2021;90:612–626